2016
DOI: 10.3389/fphys.2016.00491
|View full text |Cite
|
Sign up to set email alerts
|

Elastin in the Liver

Abstract: A characteristic feature of liver cirrhosis is the accumulation of large amounts of connective tissue with the prevailing content of type I collagen. Elastin is a minor connective tissue component in normal liver but it is actively synthesized by hepatic stellate cells and portal fibroblasts in diseased liver. The accumulation of elastic fibers in later stages of liver fibrosis may contribute to the decreasing reversibility of the disease with advancing time. Elastin is formed by polymerization of tropoelastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 160 publications
(187 reference statements)
4
47
0
1
Order By: Relevance
“…However, the potential role of elastin fiber deposition in the irreversibility of chronic liver diseases remains poorly understood. Our quantitative fibrosis data suggest that elastin fiber is a minor fibrous component in the early stages of fibrosis but may accumulate in areas of thick bridging fibrosis, fibrous septa, or venous walls at the cirrhosis stage of NAFLD, a finding that is consistent with studies on various chronic liver diseases . Our previous study attested to the positive association of higher elastin area ratios (≥3.6%) with the risk of hepatocellular carcinoma in patients with hepatitis C virus infection .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the potential role of elastin fiber deposition in the irreversibility of chronic liver diseases remains poorly understood. Our quantitative fibrosis data suggest that elastin fiber is a minor fibrous component in the early stages of fibrosis but may accumulate in areas of thick bridging fibrosis, fibrous septa, or venous walls at the cirrhosis stage of NAFLD, a finding that is consistent with studies on various chronic liver diseases . Our previous study attested to the positive association of higher elastin area ratios (≥3.6%) with the risk of hepatocellular carcinoma in patients with hepatitis C virus infection .…”
Section: Discussionsupporting
confidence: 92%
“…Our quantitative fibrosis data suggest that elastin fiber is a minor fibrous component in the early stages of fibrosis but may accumulate in areas of thick bridging fibrosis, fibrous septa, or venous walls at the cirrhosis stage of NAFLD, a finding that is consistent with studies on various chronic liver diseases. (46,47) Our previous study attested to the positive association of higher elastin area ratios (3.6%) with the risk of hepatocellular carcinoma in patients with hepatitis C virus infection. (36) In the current NAFLD cohort, 22 (24%) of 92 patients with advanced NAFLD (4 of 41 with stage 3; 18 of 51 with stage 4) had elastin area ratios greater than or equal to 3.6%, whereas none of 162 patients with early fibrosis with stages 1/2 harbored this amount of elastin in liver biopsy specimens.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…(36) The bridging pattern of fibrosis ultimately leads to encapsulation of liver lobules (regenerative nodules) that are further damaged because of vascular undersupply. (37) Hence, the reparative potential and activities of the tissue are fundamentally altered. When regenerative nodules are present, the histological criteria for liver cirrhosis are fulfilled, corresponding to fibrosis stage F4.…”
Section: Is the Total Amount As Important As Localization And Type Ofmentioning
confidence: 99%
“…The silk‐based platforms were already systematically reviewed by Kundu et al Regarding elastin, it is one of the most stable proteins of the ECM, being present in large amounts in those elastic organs such as arteries and lungs. Kanta et al suggested that the dysregulation of elastin synthesis and metabolism may be an essential cause for liver fibrosis. Laminin is a structural protein in the ECM of skeletal muscle fibers that plays an important role in tissue development, maintenance, and function regulation …”
Section: Biomaterials In Liver Regenerationmentioning
confidence: 99%